2020
DOI: 10.1177/1591019920958827
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of pediatric ischemic stroke: A single center experience and review of the literature

Abstract: Introduction Mechanical thrombectomy is standard treatment for large vessel occlusion (LVO) in adults. There are no randomized controlled trials for the pediatric population. We report our single-center experience with thrombectomy of LVO in a series of pediatric patients, and perform a review of the literature. Methods Retrospective review of consecutive pediatric thrombectomy cases between 2011 and 2018. Demographic variables, imaging data, technical aspects and clinical outcome were recorded. Results In a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 55 publications
2
13
0
4
Order By: Relevance
“…Similar outcomes like those seen by Satti et al are also echoed by subsequent systematic reviews and metaanalyses conducted by Bhatia et al and Fragata et al These systematic reviews and meta-analyses investigated the efficacy of mechanical thrombectomy for pediatric ischemic stroke due to large vessel occlusion [48,49]. The former study found that mechanical thrombectomy resulted in good long-term neurological outcomes (mRS scores between 0-2) in 87 out of 96 cases, good short-term outcomes (reduction in NIHSS by ≥ 8 points) in 55 out of 79 cases, and successful recanalization (modified Treatment in Cerebral Ischemia, mTICI, 2b/3) in 86 out of 98 cases [48].…”
Section: Mechanical Thrombectomysupporting
confidence: 66%
See 3 more Smart Citations
“…Similar outcomes like those seen by Satti et al are also echoed by subsequent systematic reviews and metaanalyses conducted by Bhatia et al and Fragata et al These systematic reviews and meta-analyses investigated the efficacy of mechanical thrombectomy for pediatric ischemic stroke due to large vessel occlusion [48,49]. The former study found that mechanical thrombectomy resulted in good long-term neurological outcomes (mRS scores between 0-2) in 87 out of 96 cases, good short-term outcomes (reduction in NIHSS by ≥ 8 points) in 55 out of 79 cases, and successful recanalization (modified Treatment in Cerebral Ischemia, mTICI, 2b/3) in 86 out of 98 cases [48].…”
Section: Mechanical Thrombectomysupporting
confidence: 66%
“…Death occurred in two patients and symptomatic intracranial hemorrhage in one patient [48]. The latter study by Fragata et al reported seven cases over a period of seven years, in which five patients had cardiac disease, two of which were under external cardiac assistance, with a median time from onset of symptoms to treatment being approximately 7 hours [49]. Mechanical thrombectomy was performed using a stentriever in 3 patients, aspiration in 3 patients, and a combined technique in one patient [49].…”
Section: Mechanical Thrombectomymentioning
confidence: 99%
See 2 more Smart Citations
“…30 In contrast, Fragata et al noticed improvements in only 57% of the subjects. 31 In the study by Sun et al, of 11 children aged below 5 years, favorable outcomes were achieved in 64% of the patients. 32 The reasons for these observations could be the time lag in the initiation of treatment and the relatively younger age of the participants.…”
Section: Discussionmentioning
confidence: 96%